A high-capacity cathode electrolyte for all-vanadium redox flow batteries
By using a combination of solid energy storage materials with tetravalent vanadium and pentavalent vanadium in all vanadium flow batteries, the problem of difficulty in increasing the concentration of redox media is solved, and the operation of the battery in a high capacity, low cost and wide temperature range is achieved.
Patent Information
- Application Number
- CN202410499682.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-24
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-04-24
AI Technical Summary
The concentration of redox medium in all vanadium flow batteries is difficult to increase, resulting in limited capacity, narrow operating temperature range and high cost, which limits the development and application of batteries.
Using low-cost solid energy storage materials as the main energy storage medium, combining tetravalent vanadium and pentavalent vanadium as redox medium, reversible redox reaction is carried out through the equilibrium potential difference between solid energy storage materials and redox medium to achieve high Capacity battery operation.
It significantly improves the capacity and energy density of the all-vanadium flow battery system, reduces the cost of electrolyte, expands the working temperature range, and achieves stable and efficient operation of the battery.
Smart Images

Figure CN118299630B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of long-term energy storage of all-vanadium liquid flow batteries, and in particular relates to a high-capacity positive electrode electrolyte for all-vanadium liquid flow batteries. Background Art
[0002] Among the existing energy storage systems in my country, all-vanadium liquid flow batteries are a highly potential large-capacity energy storage method due to their advantages such as independent adjustment of power and capacity, fast response speed, intrinsic safety, and no ion cross-contamination. In all-vanadium liquid flow batteries, the redox medium in the electrolyte is mainly vanadium ions of different valence states, and the redox medium is mainly divalent vanadium V 2+ 、Trivalent vanadium V 3+ 、Tetravalent vanadium VO 2+ and pentavalent vanadium VO2 + The vanadium ions in different valence states store and release energy. Therefore, the energy storage capacity of the vanadium flow battery can be improved by increasing the concentration of redox media in the electrolyte. However, in the sulfuric acid-supported electrolyte system, pentavalent vanadium VO2 + In contrast to the adaptability of other valence states of vanadium ions to sulfuric acid, pentavalent vanadium VO2 + The solubility is higher, but at low temperatures, due to the common ion effect of sulfate ions, divalent vanadium V 2+ 、Trivalent vanadium V 3+ and tetravalent vanadium VO 2+ It is easy to precipitate in the form of sulfate, and its solubility is limited. At the same time, at high temperature, pentavalent vanadium VO2 + When the concentration is high, V2O5 precipitation is easily generated through thermal reaction. Therefore, it is difficult to make a breakthrough in the concentration of redox media in all-vanadium flow batteries, which limits the capacity of all-vanadium flow batteries. At the same time, the operating temperature range of all-vanadium flow batteries is narrow and the cost is high, which limits the development and application of all-vanadium flow batteries. Summary of the invention
[0003] In order to solve the above problems, the present invention provides a high-capacity all-vanadium liquid flow battery positive electrode electrolyte, which adopts low-cost solid energy storage materials as the main energy storage medium, so that the capacity is not limited by the concentration of the redox medium. Even when the concentration of the redox medium is low, a higher capacity can be achieved, thereby solving the problems of low capacity, high cost and narrow working range in the prior art, and realizing stable and efficient operation of the all-vanadium liquid flow battery.
[0004] The technical solution adopted by the present invention is a high-capacity all-vanadium liquid flow battery positive electrode electrolyte, which includes: a supporting electrolyte, a solid energy storage material and tetravalent vanadium (VO 2+ ) and pentavalent vanadium (VO2 +) one or both, where VO 2+ / VO2 + The concentration is 0.1-2 mol / L, and the solid energy storage material (concentration is 0.02-1 g / mL) contains a solid energy storage substance, and the solid energy storage substance is selected from Prussian blue analogs.
[0005] The cations contained in the supporting electrolyte include ammonium ions and hydrogen ions, the anions include one or more of sulfate, chloride, nitrate, and phosphate, and water is used as a solvent, wherein the ammonium ion concentration is 0.1-1 mol / L.
[0006] The solid energy storage material is a targeted redox material, and reacts with the positive redox medium VO of the all-vanadium redox flow battery in the supporting electrolyte containing ammonium ions. 2+ / VO2 + The equilibrium potential difference is between ±120mV, and a reversible redox reaction can occur. During the reaction, ammonium ions will be embedded or removed from the structure of the solid energy storage material. The material is composed of one or two of ammonia-rich copper ferrocyanide and ammonia-rich copper ferrocyanide, which are mutually converted between the oxidized and reduced states. The molecular formula is M x Cu y (NH4) z Fe III / II (CN)6·nH2O, wherein M is selected from one or both of K and Na, and 3≤x+2y+z≤4. When the solid energy storage materials are all ammonia-enriched copper ferrocyanide, x+2y+z=3. When the solid energy storage materials are all ammonia-enriched copper ferrocyanide, x+2y+z=4.
[0007] In addition to the solid energy storage material, the solid energy storage material may also contain a conductive material (5% to 40% by mass) or a binder such as polyvinylidene fluoride (5% to 15% by mass). The conductive material is selected from one or more of powdered, sheet-like, mesh-like or foamed metal materials (nickel and titanium, etc.) or carbon materials (conductive carbon black, carbon cloth, carbon felt, carbon paper and graphite felt, etc.). The solid energy storage material is provided in the liquid storage tank in one or more solid forms of sheet, mesh, foam, solid or hollow sphere, cylinder or other polyhedron.
[0008] The present invention provides a high-capacity all-vanadium liquid flow battery positive electrode electrolyte, which has the following beneficial effects compared with the conventional all-vanadium liquid flow battery positive electrode electrolyte:
[0009] 1. Solid energy storage materials are the main capacity / energy carriers, and their theoretical concentration is close to 10 mol / L, which is much higher than the 1.5-1.7 mol / L liquid redox medium VO currently used in commercialization. 2+ / VO2 + .
[0010] 2. Positive redox mediator VO 2+ / VO2 + A lower concentration can be used, which on the one hand reduces the cost of the electrolyte, and on the other hand improves the thermal stability of the positive electrode electrolyte.
[0011] 3. By adjusting the solid energy storage material and the positive electrode redox medium VO 2+ / VO2 + The concentration can achieve control of electrolyte capacity / energy.
[0012] 4. The low-cost ammonia-rich iron / copper ferrocyanide solid energy storage material was synthesized experimentally, with a theoretical concentration of 9.45 mol / L, and it reacted with the positive electrode redox medium VO 2+ / VO2 + Reversible redox reactions can occur, and the utilization rate of solid energy storage materials can reach 64%. The high-capacity all-vanadium liquid flow battery positive electrode electrolyte disclosed in this patent can significantly improve the capacity and energy density of the all-vanadium liquid flow battery system and reduce the cost of the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 (a) is the positive electrode redox medium VO of the all-vanadium liquid flow battery 2+ / VO2 + (a) is the three-electrode system device of the all-vanadium liquid flow battery with redox medium VO 2+ / VO2 + And cyclic voltammetry curves of solid energy storage materials.
[0014] Figure 2 (a) is a schematic diagram of the in-situ liquid flow UV-visible spectroscopy test principle of the solid energy storage material; (b) is a schematic diagram of the solid energy storage material and the positive electrode redox medium VO 2+ / VO2 + Reaction schematic diagram.
[0015] Figure 3 For in-situ flow UV-visible spectroscopy testing of VO 2+ concentration change curve.
[0016] Figure 4 This is the cycle capacity diagram of the all-vanadium liquid flow cathode half-cell. DETAILED DESCRIPTION
[0017] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments, so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0018] Example 1: Preparation of solid energy storage material and determination of molecular formula
[0019] In the above high-capacity all-vanadium liquid flow battery cathode electrolyte, energy is stored in the ammonia-rich iron / copper ferrocyanide solid energy storage material. Therefore, in the first aspect of the present invention, a solid energy storage material is prepared and its molecular formula is determined. The preparation process mainly includes the following two steps:
[0020] In the first step, copper / ferrocyanide (CuHCF) was prepared by a simple mixed precipitation method. Solution A was an aqueous solution of 250 mL sodium ferrocyanide, with a concentration of 0.2 M sodium ferrocyanide; solution B was a mixed aqueous solution composed of 500 mL 0.1 M copper sulfate, 0.5 M sodium sulfate and 20.0045 g PVP K30. First, solution A was dripped into solution B drop by drop at a flow rate of 0.5 mL / min, accompanied by vigorous magnetic stirring, to obtain a reddish-brown solid; the mixed solution after the dropwise addition was allowed to stand overnight to allow the deposited solid matter to separate from the filtrate; the solid matter was separated from the filtrate under the action of a high-speed centrifuge, and the obtained solid matter was washed with ultrapure water and ethanol several times; finally, the obtained solid matter was dried under vacuum conditions at 60 ° C for 12 hours, and the dried solid was ground in an agate mortar to obtain a solid powder of CuHCF.
[0021] In the second step, ammonia-rich iron / copper ferrocyanide (NH4-CuHCF) is obtained by ion replacement. The CuHCF prepared in the first step is fully mixed with 100 mL of ammonium sulfate aqueous solution (wherein the concentration of ammonium sulfate is 0.5 M) and stirred for 6 hours, and then allowed to stand overnight; the solid obtained is NH4-CuHCF by the same separation, washing, drying and grinding method as in the first step.
[0022] ICP, elemental analysis and true density measurement were performed on NH4-CuHCF to determine the molecular formula of the substance. The measurement results showed that the true density of the substance was 3.62 g / cm 3 In this substance, the ratio of Cu to Na is 5.333, the ratio of Fe to Na is 3.365, and the proportions of N, C, H, and O are 23.67%, 19.55%, 3.509%, and 14.298%, respectively. By calculation, the molecular formula of NH4-CuHCF is: Na 0.297 Cu 1.585 (NH4) 0.229 Fe(CN)6·3.294H2O, relative molecular mass is 382.989g / mol. The theoretical charge concentration (c theoretical , mol / L) is calculated using the following equation:
[0023]
[0024] Where n is the number of electrons transferred during the reaction of the solid energy storage material, ρ is the true density of the solid energy storage material, and M is the relative molecular mass of the solid energy storage material. In this embodiment, n = 1, so the calculation is: c theoretical =9.452mol / L.
[0025] Example 2: All-vanadium redox medium VO in positive electrode of all-vanadium redox flow battery 2+ / VO2 + Cyclic voltammetry test experiment of solid energy storage materials
[0026] Cut 0.5×0.5cm 2 The carbon cloth is then prepared, NH4-CuHCF, Super P Li and PVDF are uniformly mixed in a ratio of 7:2:1, N-methylpyrrolidone is used as a solvent, the mixture is fully dispersed in the solvent, and the mixed solution is coated on the carbon cloth; the coated carbon cloth is dried in a vacuum environment at 60° C. to evaporate the solvent, and the dried carbon cloth is NH4-CuHCF-SM carbon cloth.
[0027] A three-electrode system was used to conduct cyclic voltammetry test. The experimental setup is shown in the figure below. Figure 1 As shown in (a), specifically: Ag / AgCl is the reference electrode, platinum is the counter electrode, the potential range is 0.2V to 1.4V, and the scan rate is 10mV / s. 2+ / VO2 + The electrolyte was a mixed aqueous solution of vanadyl sulfate and sulfuric acid, where the concentrations of vanadyl sulfate and sulfuric acid were 0.1 M and 2 M, respectively. 2 Graphite felt (SGL GFD 2.5EA, 500℃ 24h) was used as the working electrode. For the test of solid energy storage materials, the electrolyte was a mixed aqueous solution of ammonium sulfate and sulfuric acid, where the concentrations of ammonium sulfate and sulfuric acid were 0.5M and 2M, respectively, and NH4-CuHCF-SM carbon cloth was used as the working electrode.
[0028] Test results such as Figure 1 As shown in (b), the positive electrode redox medium VO 2+ / VO2 + The equilibrium potential E 1 / 2 =0.89V, the equilibrium potential E of NH4-CuHCF-SM 1 / 2 =0.79V, the equilibrium potential difference between the two is 100mV, and the reversibility is good.
[0029] Example 3: In-situ liquid flow UV-visible spectroscopy test of solid energy storage materials
[0030] The schematic diagram of the in-situ liquid flow UV-visible spectroscopy test and the schematic diagram of the reaction in the targeted liquid storage tank are shown in Figure 2 (a) and Figure 2 (b). In this embodiment, the chemical reaction occurring in the targeted liquid storage tank is the same as the chemical reaction occurring in the positive electrode liquid storage tank during the positive electrode charging process. The instrument used in the experiment is Shimadzu UV-2600, and the optical path of the test is 1mm. The experiment mainly detects the concentration of tetravalent vanadium, so the UV wavelength is fixed to 765mm, the total test time is 10000s, the sampling interval is 1s, and the blank control solution is a sulfuric acid aqueous solution, wherein the concentration of sulfuric acid is 2M. NH4-CuHCF, Super P Li, and PVDF are mixed evenly in a ratio of 75:15:10, N-methylpyrrolidone is added as a solvent, and the mixture is fully dispersed in the solvent, and then the mixed solution is coated on a titanium foil and dried under a vacuum environment at 60°C to evaporate the solvent. After drying, the solid on the titanium foil is separated from the titanium foil, and the obtained flaky solid is an ammonia-rich iron / copper ferrocyanide solid energy storage material (NH4-CuHCF-SM). The electrolyte in the initial storage tank is obtained by electrolyte ionization. 20mL of 0.1M VOSO4+0.5M (NH4)2SO4+2M H2SO4 solution is respectively loaded into the positive and negative storage tanks of the single cell at a volume ratio of 1:1 for ionization. The solution obtained at the positive electrode is 0.1M VO2 + +0.5M(NH4)2SO4+2M H2SO4.
[0031] 7 mL of cathode solution was added to the target storage tank of the in-situ flow UV-visible spectroscopy test. The electrolyte circulated at a flow rate of 0.5 mL / min under the action of the peristaltic pump. At this time, c(VO 2+ )=16.8mM, and there is a small amount of tetravalent vanadium in the electrolyte. At 1800s, 0.25g of ammonia-rich copper ferrocyanide solid energy storage material was added, and it can be observed that the tetravalent vanadium in the electrolyte gradually increased (such as Figure 3 As shown), the final c(VO 2+ )=79.5mM. Theoretical capacity of solid energy storage materials (C theoretical , Ah) is calculated by the following equation:
[0032]
[0033] Where m is the mass of the solid energy storage material, w is the mass fraction of the solid energy storage material in the solid energy storage material, and F is the Faraday constant (96485C / mol). Therefore, the theoretical capacity of 0.25g of solid energy storage material is calculated as C theoretical =13.1mAh.
[0034] After adding solid energy storage materials, VO 2+ The concentration of VO2 in the target storage tank increased significantly, indicating that the added solid energy storage material+ Reacts and is reduced, making VO 2+ The concentration of the added solid energy storage material is 35.71g / L, and the target storage tank is tetravalent vanadium VO 2+ The concentration change is Δc(VO 2+ )=62.7mM, that is, the storage capacity of the solid energy storage material in this process is 11.74mAh, and the storage utilization rate of the solid energy storage material is 89.65%.
[0035] Example 4: All-vanadium liquid flow cathode half-cell cycle experiment
[0036] The positive electrode symmetrical battery was assembled and constant current charging and discharging was performed with a current of 120 mA and a charge and discharge cut-off voltage of 0.4 V and -0.4 V, respectively. The ion exchange membrane was Nafion 115 and the electrode was 2×2 cm 2 The graphite felt (SGL GFD 2.5EA, 500℃24h), the positive electrolyte is 20mL 0.6M VOSO4+0.5M(NH4)2SO4+2M H2SO4, the negative electrolyte is 20mL 0.6MVOSO4+0.5M(NH4)2SO4+2M H2SO4 and 40mL 0.6M VO2 + +0.5M (NH4)2SO4+2M H2SO4 mixed solution, the preparation method of the solid energy storage material is the same as in Example 3.
[0037] The charge and discharge capacity of the battery is Figure 4 As shown in , when no solid energy storage material is added to the positive electrode reservoir, 5 charge and discharge cycles are carried out, and the basic capacity of the battery is about 318.92 mAh; before the start of the 6th cycle, 2 g of solid energy storage material is added to the positive electrode reservoir, the concentration of the solid energy storage material is 0.1 g / mL, and the theoretical capacity is 104.79 mAh. The capacity of the battery is increased to 359.53 mAh and remains stable, which is equivalent to adding VO2 in the positive electrode electrolyte. 2+ / VO2 + The concentration of VO2 in the positive electrode electrolyte was increased to 0.672 mol / L, the battery capacity increased by 40.61 mAh, and the utilization rate of the solid energy storage material was 38.75%; before the start of the 14th cycle, 2 g of solid energy storage material was added to the positive electrode storage tank again, and the battery capacity increased to 452.79 mAh and remained stable, which was equivalent to reducing the VO2 in the positive electrode electrolyte to 0.672 mol / L. 2+ / VO2 + The concentration was increased to 0.846 mol / L, which was a total increase of 133.87 mAh compared to the basic capacity, and the utilization rate of the total solid energy storage material was 63.88%.
Claims
1. A high-capacity all-vanadium redox flow battery cathode electrolyte, characterized in that: include: Supporting electrolytes, solid energy storage materials, and tetravalent vanadium VO as redox mediator 2+ and pentavalent vanadium VO2 + One or two of the above, wherein the solid energy storage material comprises a solid energy storage material selected from Prussian blue analogs; The cations contained in the supporting electrolyte include ammonium ions and hydrogen ions; The anions contained in the supporting electrolyte species include one or more of sulfate, chloride, nitrate, and phosphate; The supporting electrolyte uses water as a solvent; The equilibrium potential of the solid energy storage material in the supporting electrolyte is VO 2+ / VO2 + The equilibrium potential difference is between ±120 mV, and the solid energy storage material undergoes a reversible redox reaction with the positive electrode redox medium; The solid energy storage material is composed of one or two of ammonia-rich copper ferrocyanide and ammonia-rich copper ferrocyanide, which are mutually convertible between oxidation and reduction states, and the molecular formula is M x Cu y (NH4) z Fe(CN)6·nH2O, wherein M is selected from one or both of K and Na, and 3≤x+2y+z≤4; The concentration of the solid energy storage material is 0.02-1 g / mL.
2. The high-capacity all-vanadium redox flow battery positive electrolyte according to claim 1, characterized in that: The ammonium ion concentration is 0.1-1 mol / L.
3. The high-capacity all-vanadium redox flow battery positive electrolyte according to claim 1, characterized in that: The redox mediator VO 2+ / VO2 + The concentration is 0.1~2mol / L.
4. The high-capacity all-vanadium redox flow battery positive electrolyte according to claim 1, characterized in that: The solid energy storage material further comprises a conductive material, the mass fraction of which is 5% to 40%, and the conductive material is selected from one or more metal materials or carbon materials in powder, sheet, mesh or foam form.
5. The high-capacity all-vanadium redox flow battery positive electrolyte according to claim 4, characterized in that: The metal material is selected from one or both of nickel and titanium, and the carbon material is selected from one or more of conductive carbon black, carbon cloth, carbon felt, carbon paper and graphite felt.
6. The high-capacity all-vanadium redox flow battery positive electrolyte according to claim 1, characterized in that: The solid energy storage material further comprises a binder, the mass fraction of which is 5% to 15%.
7. The high-capacity all-vanadium redox flow battery positive electrolyte according to claim 1, characterized in that: The solid form of the solid energy storage material includes but is not limited to one or more of sheet, grid, foam, solid or hollow sphere, cylinder or other polyhedron.
Citation Information
Patent Citations
All-vanadium redox flow battery system
CN117117273A
Cited By
All-vanadium redox flow battery composite electrolyte containing multi-electron additive and preparation method of all-vanadium redox flow battery composite electrolyte
CN122025717A
Vanadium-bromine flow battery based on dual solid-phase energy storage mechanism
CN122511944A
Solid energy storage material for vanadium redox flow battery, preparation method of solid energy storage material, positive electrode electrolyte and vanadium redox flow battery
CN122599474A
A flow battery with solid phase energy storage mechanism
CN122696728A